Potential Impact of Prosthetic Biomaterials on the Periodontium: A Comprehensive Review - Alarcón-Sánchez, Mario Alberto; Heboyan, Artak; Fernandes, Gustavo Vicentis de Oliveira; Castro-Alarcón, Natividad; Romero-Castro, Norma Samanta (Molecules (Basel, Switzerland), 2023)
The success of a prosthetic treatment is closely related to the periodontal health of the individual. The aim of this article was to review and present the importance of prosthetic restorative materials on the condition of the periodontium, the changes that occur in the composition of the subgingival microbiota and the levels of inflammatory markers in gingival crevicular fluid. Articles on the influence of different prosthetic restorative materials on subgingival microbiota and proinflammatory cytokines were searched for using the keywords “prosthetic biomaterials”, “fixed prosthesis”, “periodontal health”, “subgingival microbiota”, “periodontal biomarkers” and “gingival crevicular fluid” in PubMed/Medline, Science Direct, Scopus and Google Scholar. The type of material used for prosthesis fabrication together with poor marginal and internal fit can result in changes in the composition of the subgingival microbiota, as well as increased accumulation and retention of dentobacterial plaque, thus favoring the development of periodontal disease and prosthetic treatment failure. Biological markers have helped to understand the inflammatory response of different prosthetic materials on periodontal tissues with the main purpose of improving their clinical application in patients who need them. Metal-free ceramic prostheses induce a lower inflammatory response regardless of the fabrication method; however, the use of CAD/CAM systems is recommended for their fabrication. In addition, it is presumed that metal-ceramic prostheses cause changes in the composition of the subgingival microbiota producing a more dysbiotic biofilm with a higher prevalence of periodontopathogenic bacteria, which may further favor periodontal deterioration.